Highly potent artemisinin-derived dimers and trimers: Synthesis and evaluation of their antimalarial, antileukemia and antiviral activities. - Reiter, Christoph; Fröhlich, Tony; Gruber, Lisa; Hutterer, Corina; Marschall, Manfred; Voigtländer, Cornelia; Friedrich, Oliver; Kappes, Bärbel; Efferth, Thomas; Tsogoeva, Svetlana (Bioorganic & medicinal chemistry, 2015)
New pharmaceutically active compounds can be obtained by modification of existing drugs to access more effective agents in the wake of drug resistance amongst others. To achieve this goal the concept of hybridization was established during the last decade. We employed this concept by coupling two artemisinin-derived precursors to obtain dimers or trimers with increased in vitro activity against Plasmodiumfalciparum 3D7 strain, leukemia cells (CCRF-CEM and multidrug-resistant subline CEM/ADR5000) and human cytomegalovirus (HCMV). Dimer 4 (IC50 of 2.6nM) possess superior antimalarial activity compared with its parent compound artesunic acid(3) (IC50 of 9.0nM). Dimer5 and trimers6 and 7 display superior potency against both leukemia cell lines (IC50 up to 0.002μM for CCRF-CEM and IC50 up to 0.20μM for CEM/ADR5000) and are even more active than clinically used doxorubicin (IC50 1.61μM for CEM/ADR5000). With respect to anti-HCMV activity, trimer6 is the most efficient hybrid (IC50 0.04μM) outperforming ganciclovir (IC50 2.6μM), dihydroartemisinin(IC50 >10μM) and artesunic acid (IC50 3.8μM).
Keywords: Artemisinin-derived hybrids; Artemisinin-derived dimers; Artemisinin-derived trimers; Antimalarial activity; Anticancer activity; Antiviral activity

New efficient artemisinin derived agents against human leukemia cells, human cytomegalovirus and Plasmodium falciparum: 2nd generation 1,2,4-trioxane-ferrocene hybrids. - Reiter, Christoph; Fröhlich, Tony; Zeino, Maen; Marschall, Manfred; Bahsi, Hanife; Leidenberger, Maria; Friedrich, Oliver; Kappes, Bärbel; Hampel, Frank; Efferth, Thomas; Tsogoeva, Svetlana (European journal of medicinal chemistry, 2015)
In our ongoing search for highly active hybrid molecules exceeding their parent compounds in anticancer, antimalaria as well as antiviral activity and being an alternative to the standard drugs, we present the synthesis and biological investigations of 2nd generation 1,2,4-trioxane-ferrocene hybrids. In vitro tests against the CCRF-CEM leukemia cell line revealed di-1,2,4-trioxane-ferrocene hybrid 7 as the most active compound (IC50 of 0.01 μM). Regarding the activity against the multidrug resistant subline CEM/ADR5000, 1,2,4-trioxane-ferrocene hybrid 5 showed a remarkable activity (IC50 of 0.53 μM). Contrary to the antimalaria activity of hybrids 4-8 against Plasmodium falciparum 3D7 strain with slightly higher IC50 values (between 7.2 and 30.2 nM) than that of their parent compound DHA, hybrids 5-7 possessed very promising activity (IC50 values lower than 0.5 μM) against human cytomegalovirus (HCMV). The application of 1,2,4-trioxane-ferrocene hybrids against HCMV is unprecedented and demonstrated here for the first time.
Keywords: Artemisinin; Ferrocene; Hybrid; Cancer; Malaria; Human cytomegalovirus

Synthesis of Novel Hybrids of Thymoquinone and Artemisinin with High Activity and Selectivity Against Colon Cancer - Fröhlich, Tony; Ndreshkjana, Benardina; Muenzner, Julienne K.; Reiter, Christoph; Hofmeister, Elisabeth; Mederer, Sandra; Fatfat, Maamoun; El Baba, Chirine; Gali-Muhtasib, Hala; Schneider-Stock, Regine; Tsogoeva, Svetlana (ChemMedChem, 2017)
Colorectal cancer causes 0.5 million deaths each year. To combat this type of cancer the development of new specific drug candidates is urgently needed. In the present work seven novel thymoquinone-artemisinin hybrids with different linkers were synthesized and tested for their in vitro anticancer activity against a panel of various tumor cell lines. The thymoquinone-artesunic acid hybrid 7 a, in which both subunits are connected via an ester bond, was found to be the most active compound and selectively decreased the viability of colorectal cancer cells with an IC50 value of 2.4 ?m (HCT116) and 2.8 ?m (HT29). Remarkably, hybrid 7 a was up to 20-fold more active than its parent compounds (thymoquinone and artesunic acid), while not affecting nonmalignant colon epithelial HCEC cells (IC50 >100 ?m). Moreover, the activity of hybrid 7 a was superior to that of various 1:1 mixtures of thymoquinone and artesunic acid. Furthermore, hybrid 7 a was even more potent against both colon cancer cell lines than the clinically used drug 5-fluorouracil. These results are another excellent proof of the hybridization concept and confirm that the type and length of the linker play a crucial role for the biological activity of a hybrid drug. Besides an increase in reactive oxygen species (ROS), elevated levels of the DNA-damage marker ?-H2AX were observed. Both effects seem to be involved in the molecular mechanism of action for hybrid 7 a in colorectal cancer cells.
EVALuna2:6899

Synthesis of Thymoquinone-Artemisinin Hybrids: New Potent Antileukemia, Antiviral, and Antimalarial Agents - Fröhlich, Tony; Reiter, Christoph; Saeed, Mohamed E. M.; Hutterer, Corina; Hahn, Friedrich; Leidenberger, Maria; Friedrich, Oliver; Kappes, Bärbel; Marschall, Manfred; Efferth, Thomas; Tsogoeva, Svetlana (ACS Medicinal Chemistry Letters, 2018)
A series of hybrid compounds based on the natural products artemisinin and thymoquinone was synthesized and investigated for their biological activity against the malaria parasite Plasmodium falciparum 3D7 strain, human cytomegalovirus (HCMV), and two leukemia cell lines (drug sensitive CCRF-CEM and multidrug-resistant subline CEM/ADR5000). An unprecedented one-pot method of selective formation of C-10 alpha-acetate 14 starting from a 1:1 mixture of C-10 alpha- to C-10 beta-dihydroartemisinin was developed. The key step of this facile method is a mild decarboxylative activation of malonic acid mediated by DCC/DMAP. Ether-linked thymoquinone artemisinin hybrids 6a/b stood out as the most active compounds in all categories, while showing no toxic side effects toward healthy human foreskin fibroblasts and thus being selective. They exhibited EC50 values of 0.2 mu M against the doxorubicin-sensitive as well as the multidrug-resistant leukemia cells and therefore can be regarded as superior to doxorubicin. Moreover, they showed to be five times more active than the standard drug ganciclovir and nearly eight times more active than artesunic acid against HCMV. In addition, hybrids 6a/b possessed excellent antimalarial activity (EC50 = 5.9/3.7 nM), which was better than that of artesunic acid (EC50 = 8.2 nM) and chloroquine (EC50 = 9.8 nM). Overall, most of the presented thymoquinone artemisinin-based hybrids exhibit an excellent and broad variety of biological activities (anticancer, antimalarial, and antiviral) combined with a low toxicity/high selectivity profile.
EVALuna2:35278

The broad-spectrum antiinfective drug artesunate interferes with the canonical nuclear factor kappa B (NF-κB) pathway by targeting RelA/p65 - Hutterer, Corina; Niemann, Ina; Milbradt, Jens; Fröhlich, Tony; Reiter, Christoph; Kadioglu, Onat; Bahsi, Hanife; Zeitträger, Isabel; Wagner, Sabrina; Einsiedel, Jürgen; Gmeiner, Peter; Vogel, Nicolas; et al. (Antiviral Research, 2015)
Infection with human cytomegalovirus (HCMV) is a serious medical problem, particularly in immunocompromised individuals and neonates. The success of standard antiviral therapy is hampered by low drug compatibility and induction of viral resistance. A novel strategy is based on the exploitation of cell-directed signaling inhibitors. The broad antiinfective drug artesunate (ART) offers additional therapeutic options such as oral bioavailability and low levels of toxic side-effects. Here, novel ART-derived compounds including dimers and trimers were synthesized showing further improvements over the parental drug. Antiviral activity and mechanistic aspects were determined leading to the following statements: (i) ART exerts antiviral activity towards human and animal herpesviruses, (ii) no induction of ART-resistant HCMV mutants occurred in vitro, (iii) chemically modified derivatives of ART showed strongly enhanced anti-HCMV efficacy, (iv) NF-κB reporter constructs, upregulated during HCMV replication, could be partially blocked by ART treatment, (v) ART activity analyzed in stable reporter cell clones indicated an inhibition of stimulated NF-κB but not CREB pathway, (vi) solid-phase immobilized ART was able to bind to NF-κB RelA/p65, and (vii) peptides within NF-κB RelA/p65 represent candidates of ART binding as analyzed by in silico docking and mass spectrometry. These novel findings open new prospects for the future medical use of ART and ART-related drug candidates.
Keywords: Artesunate and chemical derivatives; Binding of artesunate to NF-κB RelA/p65; Broad antiviral activity; Human cytomegalovirus; Increase of antiviral efficacy; Interference with NF-κB signaling pathways